LINGUISTIC AND CULTURAL VARIATIONS AS BARRIERS TO THE TEFL SETTINGS IN PAPUA - Yohana Susana Yembise (TEFLIN, 2011)
The article aims at presenting a description of languages and cultures and the effect on the teaching of English as a Foreign Language in schools in Papua. It starts with a general picture of the uniqueness of languages and cultures in Papua: its geography, the originality of the people, and the languages and cultures of both NAN and AN. The word âPapuaâ (used to be called Irian Jaya) in the above title is the name of the Eastern Province in Indonesia. The article further presents ongoing controversial issues on the impact of linguistic and cultural diversity in Papua towards the educational development including the TEFL program in this province.Â It then provides alternative solutions as reflected in the pedagogical implications to be employed in multicultural classrooms particularly in Papua.